Non-modifiable and modifiable factors contributing to recurrent stroke: A systematic review and meta-analysis - Ricvan Dana Nindrea; Asni Hasanuddin (Elsevier, 2023)
Background: The risk factors for recurrent stroke are multi-factorial. It is important to identify risk factors contributing to recurrent stroke in order to produce effective preventive measurement. This study aims to find non-modifiable and modifiable factors contributing to recurrent stroke. Methods: A Systematic review of studies on non-modifiable and modifiable factors contributing to recurrent stroke in the PubMed, ProQuest, and EBSCO were employed to search related articles published from January 2010 to January 2021. The Pooled Hazard Ratio (PHR) of the risk factors were calculated by using fixed and random-effect models. The heterogeneity was computed by calculation of I2. Publication bias was assessed using Egger's test. All data processing and analysis were performed using STATA 16.0. Results: Modifiable risk factors contributing to recurrent stroke included ischemic heart disease (PHR = 2.78 [95% CI 1.91-6.47]), atrial fibrillation (PHR = 1.87 [95% CI 1.23-2.52]), hypertension (PHR = 1.66 [95% CI] 1.15-2.17]), and obesity (PHR = 0.85 [95% CI] 0.78-0.92]). Non-modifiable risk factor associated to recurrent stroke was older age (PHR = 1.03 [95% CI 1.02-1.04]). The heterogeneity calculation showed homogenous among studies in hypertension, obesity and older age (I2 ≤ 50%). Conclusion: Ischemic heart disease, atrial fibrillation, hypertension, obesity and older age contribute to recurrent stroke. Thus, prevention measurements for recurrent stroke are suggested in patients with these conditions.